Some Observations on the Viscosity of Pathological Human Blood Plasma - Dintenfass, L (Thrombosis and Haemostasis, 1965)
Viscosities of blood plasma obtained from patients suffering from leukaemia, macroglobulinaemia, polycythaemia, spherocytosis, haemophilia and myelofibrosis has been studied by means of a rotational cone-in-cone viscometer. The data obtained is not intended to characterize the specific diseases. The aim is to show that a great range of viscosities may be found in various samples of human blood plasma and that the pathological plasma may show non-Newtonian and thixotropic flow characteristics.It is suggested that determination of plasma viscosities, over a range of rates of shear, might contribute to our understanding of some problems of blood circulation and might be beneficial in more correct evaluation of the erythrocyte sedimentation tests.